ASP-Based Time-Bounded Planning for Logistics Robots - Schäpers, Björn; Niemueller, Tim; Lakemeyer, Gerhard; Gebser, Martin; Schaub, Torsten (Proceedings of the International Conference on Automated Planning and Scheduling, 2018)
Manufacturing industries are undergoing a major paradigm shift towards more autonomy. Automated planning and scheduling then becomes a necessity. The Planning and Execution Competition for Logistics Robots in Simulation held at ICAPS is based on this scenario and provides an interesting testbed. However, the posed problem is challenging as also demonstrated by the somewhat weak results in 2017. The domain requires temporal reasoning and dealing with uncertainty. We propose a novel planning system based on Answer Set Programming and the Clingo solver to tackle these problems and incentivize robot cooperation. Our results show a significant performance improvement, both, in terms of lowering computational requirements and better game metrics.